BREEDING FIELD CROPS FOR ORNAMENTAL PURPOSE: A CASE IN Jatropha spp. - Muakrong, Narathid; Phetcharat, Chamnanr; Tanya, Patcharin; Srinives, Peerasak (AGRIVITA, Journal of Agricultural Science, 2014)
Populations of F1, F2 and BC1F1 were formed from an interspecific cross between green-flowered Jatropha curcas and red-flowered J. integerrima (dwarf type) to observe for segregation in flower colors and to select for ornamental segregants. The crossing to produce F1 and BC1F1 was successful only when J. curcas was used as the female parent. The suitable time for crossing was between 08:00 â 13:00 oâclock with fruit setting rate of 65-78%. The F1 segregated into white- and pink-flowered plants. While flowers of the F2 population segregated into nine different colors, viz. light green, green, white, very light pink, light pink, pink, deep pink, very deep pink, and red. When J. curcas was backcrossed by a pink-flowered F1, its BC1F1 progenies segregated into green, light green, white, very light pink and light pink flowers. While another set of BC1F1 progenies obtained from a white-flowered F1 parent segregated into green, light green, and white. The segregating progenies in both sets showed smaller plants than jatropha and bore colorful flowers suitable for ornamental purpose. Six plants were chosen and registered at Kasetsart University and the Thai Department of Agriculture as commercial cultivars, âKamphaeng Saen 1â to âKamphaeng Saen 6â.Â Keywords: ornamental jatropha, interspecific cross, flower color, crossing durations Â Â Â Â Â Â Â Â Â Â